FREQUENCY OF IRON DEFICIENCY ANEMIA IN NON-DIALYSIS CHRONIC KIDNEY PATIENTS - Khan, Merina; Mahmood, Syed Nayyer; Fatima, Novara (Pakistan Journal of Kidney Diseases, 2022)
Background: Iron deficiency anemia (IDA) is the most common type of anemia. In chronic kidney disease (CKD) patients, it’s a significant burden and becomes more prevalent with decreasing GFR. Though, erythropoietin deficiency remains the major cause of anemia in CKD patients due to decreased renal erythropoietin production, yet the frequency of IDA in pre-dialysis CKD patients has not been well established in Pakistan. Objective: To determine the frequency of IDA in pre-dialysis CKD patients. Materials and Methods: 188 pre-dialysis CKD patients of age 18-75 and both genders were included. Patients having obvious causes of anemia were excluded. The percentage of patients with IDA in pre-dialysis CKD was then determined during OPD follow up. Results: Mean age was 46.03±12.24 years. Out of 188 patients, 102 (54.26%) were males with male-female ratio of 1.2:1. The frequency of IDA in pre-dialysis CKD patients was found in 73 (38.83%) patients. Conclusion: Study concluded that frequency of IDA in pre-dialysis CKD patients is high and close attention to the causes and its replacement may improve the patient outcome. Keywords: CKD, Pre-dialysis , IDA, anemia